Metabolic syndrome in children and adolescents: definitions, epidemiology, pathophysiology, interventions, and challenges - Zhang, Baoquan; Shi, Huiying; Cai, Wenhong; Yang, Bin; Xiu, Wenlong (Frontiers in Endocrinology, 2025)
Metabolic syndrome (MetS) is a group of cardiometabolic risk factors with high prevalence in the adult population. To date, there is no consensus on the definition for MetS in children and adolescents despite the presence of well-established diagnostic criteria in adults. The etiology of MetS is associated with a complex interaction between genetic susceptibility and environmental factors, in which the modifiable environmental risk factors are considered to play an important role in this process. MetS is significantly associated with an increased risk of diabetes mellitus and cardiovascular diseases (CVDs). Thus, it is necessary to pay attention to the prevention of MetS in childhood and adulthood. Given the current epidemic of obesity in children and adolescents, there is an urgent need to provide adequate guidelines for the definition, screening, and treatment strategies of MetS in younger patients. In this narrative review, we provide some diagnostic criteria and epidemiological studies and highlight the pathogenesis and management of MetS.